A comprehensive European database of tasks indices for socio-economic research - Martina Bisello; Marta Fana; Enrique Fernández-Macías; Sergio Torrejón Pérez (European Commission, Joint Research Centre (JRC), 2021)
This paper presents a new and enriched version of the European database of tasks indices across jobs in the EU15 (minus UK) economy using most recent data from European Working Conditions Survey (EWCS 2015), a European (Italian) version of the O*NET database of occupational contents (ICP 2012) and the OECD's PIAAC Survey. The database of tasks indicators was created based on a coherent and comprehensive taxonomy of tasks contents, methods and tools developed in Fernández-Macías and Bisello (2020), which builds on the original version published in Fernández-Macías et al., (2016a, 2016b) including several additional new concepts and indicators at different levels. After a detailed description of the construction of the database and an initial assessment of its internal consistency, the paper offers an analysis of the tasks distribution across occupations and sectors at the European level, providing useful insights of work content and organisational methods prevailing along the job structure. The possibility to dig into the complexity of work activities characterizing single jobs allow to identify patterns of correlation across task indices and to better understand how tasks are bundled across occupations by sectors pairs. The empirical analysis confirms that tasks are not isolated forms of labour inputs that just happen to be in productive processes but building blocks of coherently constructed jobs which are embedded in productive organisations. Any analysis of tasks which focuses on a particular type in isolation risks missing important connections with other types of task content and forms of work organisation. We hope that our contribution raises awareness of the importance of having good and detailed measures of tasks contents, consistently measured at the individual worker level and at different points in time, in order to understand better how technical change and other factors are continuously changing the nature of work and the associated skills demand and job quality. A future European tasks survey could precisely provide that.
Keywords: 330; tasks; employment structure; European labour market; work organisation